A Comparison of the Antinociceptive Properties of SJP-005 and Morphine in Rats - Joris C Verster; Andrew Scholey; Thomas A Dahl; Jacqueline M Iversen (MDPI AG, 2021)
SJP-005 (a combination of ketotifen and ibuprofen) is being developed as a potential treatment for pain and for opioid use disorder. It is therefore important to investigate the potential antinociceptive properties of SJP-005. Two studies were conducted to evaluate the potential effects of SJP-005 in rats. Study 1 applied the von Frey test to examine the antinociceptive effect of morphine with and without SJP-005 in adjuvant-induced hypersensitivity to tactile stimulation. In a double-blind, between-groups design, groups of rats (n = 10 each) received morphine at 3, 10, or 30 mg/kg bodyweight (bw) (subcutaneous injection) with or without SJP-005 (oral). Mechanic allodynia and paw volume were assessed before and after treatment. Study 2 utilized the hot plate test. Using a crossover design, groups of rats (n = 10 each) received either morphine at 3, 10, or 30 mg/kg bw (subcutaneous injection) preceded by oral administration of placebo (Week 1) or SJP-005 (Week 2). In Study 1, in the von Frey up-and-down test, Δ paw withdrawal responses in Group 1 (3 mg/kg bw morphine) were significantly lower compared to those in Group 4 (3 mg/kg bw morphine plus SJP-005), whereas the differences in Δ paw withdrawal between Group 2 and Group 5 (10 mg/kg bw morphine with and without SJP-005) and between Group 3 and Group 6 (10 mg/kg bw morphine with and without SJP-005) did not reach statistical difference. Trendline analysis of the dose-response relationship for the morphine + placebo groups and morphine + SJP-005 groups revealed no significant differences in the intercepts and slopes. In Study 2, no significant differences were observed on hot plate performance between morphine and morphine in combination with SJP-005. In conclusion, the findings in the von Frey up-and-down test (Study 1) suggest that animals can withstand higher levels of painful stimuli when SJP-005 is co-administered. This may also suggest a possible opioid sparing effect. However, in the hot plate test (Study 2), animals did not respond more adaptively to stronger painful stimuli after co-administering SJP-005. These observations warrant further investigation of the antinociceptive properties of SJP-005.